2015
DOI: 10.1136/bmjopen-2014-006674
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of the prevalence of clinical depression and anxiety in patients with prostate cancer undergoing active surveillance

Abstract: ObjectiveTo quantitatively determine the prevalence of anxiety and depression in men on active surveillance (AS).DesignCross-sectional questionnaire survey.SettingSecondary care prostate cancer (PCa) clinics across South, Central and Western England.Participants313 men from a total sample of 426 with a histological diagnosis of PCa currently managed with AS were identified from seven UK urology departments. The mean age of respondents was 70 (51–86) years with the majority (76%) being married or in civil partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 24 publications
3
80
0
1
Order By: Relevance
“…Kohler et al (2014) T A B L E 2 (Continued) cancer patients living with and without partners and that they conducted first-time data collection 1 day before in-hospital radical prostatectomy. Such patients may have experienced intense anxiety because of their marital partnerships (Watts et al, 2015) and their situations (Hinz et al, 2009). The present study also supports the findings of Chen et al (2015) that Taiwanese patients with prostate cancer suffer from high depressive disorders; the reported findings further fill the knowledge gap regarding the prevalence of depression among patients with prostate cancer within 1 year after diagnosis in Taiwan.…”
Section: Discussionsupporting
confidence: 87%
“…Kohler et al (2014) T A B L E 2 (Continued) cancer patients living with and without partners and that they conducted first-time data collection 1 day before in-hospital radical prostatectomy. Such patients may have experienced intense anxiety because of their marital partnerships (Watts et al, 2015) and their situations (Hinz et al, 2009). The present study also supports the findings of Chen et al (2015) that Taiwanese patients with prostate cancer suffer from high depressive disorders; the reported findings further fill the knowledge gap regarding the prevalence of depression among patients with prostate cancer within 1 year after diagnosis in Taiwan.…”
Section: Discussionsupporting
confidence: 87%
“…This is important as Watts et al (2015), in a study of 313 men on active surveillance for prostate cancer, reported significantly higher levels of anxiety compared to that found in the general population. Men who underwent surgery and brachytherapy also scored well in this domain; however, men who undertook active surveillance scored poorly (p = 0·019).…”
Section: Discussionmentioning
confidence: 84%
“…Fear, anxiety, depression, reduced self-esteem and altered body image are recognized by many authors as having a negative effect on men with a diagnosis of prostate cancer (Chien et al, 2013;Hansen et al, 2013;Lassen et al, 2013;Watts et al, 2015). Fear, anxiety, depression, reduced self-esteem and altered body image are recognized by many authors as having a negative effect on men with a diagnosis of prostate cancer (Chien et al, 2013;Hansen et al, 2013;Lassen et al, 2013;Watts et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…[20] Another problem for these AS patients is anxiety. Analysis made by Watts et al [21] revealed that these patients have higher rates of anxiety and depression than that expected. Up to 33% of the patients who underwent RP on AS had PSMs.…”
Section: Discussionmentioning
confidence: 99%